THE ROLE OF FAMILY AND MEDICAL PERSONNEL IN CARING FOR TYPE 2 DIABETES PATIENTS AT IBNU SINA HOSPITAL, PASAMAN BARAT - Lula Mustafa; Rakhmadsyah Putra Rangkuty; Fauzi; Amiruddin Ketaren; Alwi (Jurnal Transparansi Publik (JTP), 2026)
This study examines the role of families in caring for type 2 diabetes patients at Ibnu Sina Simpang Empat Hospital, Kabupaten Pasaman Barat and examines the role of medical personnel in treating type 2 diabetes patients at Ibnu Sina Simpang Empat Hospital, West Pasaman Regency. The research problem in this study is to find out how the role of families in treating type 2 diabetes patients at Ibnu Sina Simpang Empat Hospital, West Pasaman Regency and the role of medical personnel in treating type 2 diabetes patients at Ibnu Sina Simpang Empat Hospital, West Pasaman Regency. This study uses Role Theory by Soerjono Soekanto. The research method used in this study is a qualitative research method. The results obtained from this study show that the family has a central role in caring for type 2 diabetes patients, especially in terms of dietary arrangements, emotional support, and treatment assistance. Meanwhile, medical personnel play the role of service providers as well as educators who provide an understanding of diabetes management. Collaboration with families and medical personnel has been shown to be effective in supporting patient recovery, lowering stress, improving medication adherence, and helping with adaptation to chronic conditions.